THE FEASIBILITY OF RICE FARMING WITH PANCA KELOLA RAMAH LINGKUNGAN TECHNOLOGY AT RAINFED RICE FIELDS IN PATI REGENCY - Ika Ferry Yunianti; Eko Haryono; Eko Hanudin; Mas Teddy Sutriadi (Agric, 2022)
Rice productivity and farmers incomes in rainfed fields could be increased through the implementation of adaptive and site-spesific technology. The technology package namely Panca Kelola Ramah Lingkungan which consists of application rice high yield, site-specific nutrient management, organic matters management, arrangement of plant spacing, and integrated pest control. This study was aimed to analyze the feasibility of rice farming with Panca Kelola Ramah Lingkungan technology at rainfed fields. The research was carried out on rainfed fields at Sukopuluhan Village, Pucakwangi District, Pati Regency in March-June 2021. Data were collected from fields experiments and interviews to 50 farmers using questionnaires. The results showed that the implementation of Panca Kelola Ramah Lingkungan technology package with Inpari 38, Inpari 39, and Inpari 41, and Inpari 32 has B/C ratio 1.23; 1.38; 1.27; and 1.51 respectively. The implementation of this technology was financially profitable and very potential to be develop in rainfed rice fields.